INTERVENSI MILITER AMERIKA SERIKAT DALAM KONFLIK SURIAH TAHUN 2011 - Syuryansyah, Syuryansyah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The United States military intervention in the 2011 Syrian conflict has sparked controversy in the international community. Some parties support the military intervention, viewing it as an effective way to protect civilians, reduce violence, and support opposition groups fighting against the Assad government. However, others oppose the military intervention, viewing it as an action that can increase the number of civilian casualties, escalate tensions between nations, worsen the humanitarian situation in the region, and create an environment that fosters terrorism. This research aims to analyze the reasons and impacts of the United States military intervention in the 2011 Syrian conflict from a positive and negative perspective. The method used is a literature review, collecting data from various sources such as academic journals, books, online articles, and other related sources. The research shows that the United States military intervention in Syria was triggered by political and economic interests and has both positive and negative consequences. Positively, the intervention was able to provide protection for civilians, reduce violence, and support opposition groups. However, there were negative impacts such as an increase in the number of civilian casualties, escalation of tensions between nations, worsening of the humanitarian situation in the region, and the creation of an environment that fosters terrorism.